DAMPAK UU ITE TERHADAP INTERAKSI MASYARAKAT DI MEDIA SOSIAL - Ade Bintang Muliya; Alpan Nuggraha; Fauzan Aulia; Aldi Pratama; Sio Antara Teguh Sihombing (Legal System Journal, 2024)
Social media has a huge influence on society, especially in legal interactions as well as social interactions, both positive and negative. The positive impact is that it provides convenience in accessing information from outside quickly, and also provides more ways to develop social skills also in formal education. Since the Law relating to Information and Electronic Transactions (ITE) was implemented, there have been several restrictions created in terms of interaction between fellow social media users. This is intended to provide security so that the virtual environment in Indonesia, especially social media, is always clean, productive and ethical. The emergence of this new law has also become a new polemic among society, more precisely regarding freedom of expression. Those who feel restricted in society feel that there is abuse of the ITE Law by officials who silence any public criticism of state officials on social media. The higher the development of the digital world and information technology, the more will also have a big impact on Indonesian society. The journal aims to find out what impacts arise in the way people interact on social media from the ITE Law. Does the ITE Law have a good or bad impact on society and how is it implemented in the real world?